Study results on species compsition of bugs (Heteroptera) in Phong Nha - Ke Bang national park, Quang Binh province - Khuong, Dang Duc; Thu Huong, Nguyen Thi (Academia Journal of Biology, 2014)
The present paper deals with the Bugs (Heteroptera) in Phong Nha - Ke Bang National Park, Quang Binh province collected from 2006 to 2008. There are 53 genera and 71 species bugs (Heteroptera) in Phong Nha - Ke Bang National Park they belonging to 10 families, in which Coreidae family with 21 species representing 29,5%, Reduviidae family18 species representing 25.3%, Pentatomidae family with 1 species representing 15,4% and Belostomatidae, Colobathristidae, Cydnidae, Lygaedae, Pyrrhocoridae, Scuteleridae, Plataspidae families with 21 species representing 29.6%. Among them 9 genera (Adrisa, Lachnophorus, Pamera, Vertomannus, Critheus, Macroceroea, Epidau, Neocentrocnemis, Rhihirbus) (17%) and 23 species (Phaenacantha bicolor, Homoeocerus impunctus, Lachnophorus cingalensis, Nysius ceylanicus, Pamera pallicornis, Vertomannus brevicollum, Vertomannus validus, Critheus lineatifrons, Dolycoris indicus, Tollumnia latipes, Tollumnia maxima, Dindymus allicornis, Macroceroea grandis, Physopelta robusta, Acanthaspis quinquespinosa, Biaticus minus, Ectrychotes comottoi, Epidau nebulo, Neocentrocnemis stali, Rhihirbus trochatericus, Sycanus szechuanus, Sycanus croceus, Chrysocoris dilaticollis) (32.4% of the species) are newly contributed to the Heteroptera entomofauna of Vietnam. In which Lethocerus indicus is a threatened species, that need seriously protection and listed in the Red Book of Vietnam.